Obesity and the Rate of Time Preference: Is there a Connection? - John Komlos; Patricia K. Smith; Barry Bogin (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
We hypothesize that recent trends in U.S. and worldwide obesity are, in part, related to an increase in the marginal rate of time preference, where time preference refers to the rate at which people are willing to trade current benefit for future benefit. The higher the rate of time preference, the larger is the factor by which individuals discount the future health risks associated with current consumption. Data from the United States, as well as international evidence, suggests that a relationship between these two variables is plausible. We encourage researchers to explore the possible link between obesity and time preference, as important insights are likely to result.
urn:nbn:de:bvb:19-epub-60-9
Keywords: I12; 330; time preference; obesity